Enhancing Financial Education: Debt-Taking And Charity-Giving Context In Indonesia - Arsyianti, Laily Dwi; Kassim, Salina; Adeyemi, Adewale Abideen (Li Falah: Journal of Islamic Economics and Business, 2018)
The low-income households are perceived to have the right to take debt from excessfinanced group or entitled for some charity. However, this perception has blur their attitude towards charity-giving. Low-income should not consider themselves as 'the taker' in perpetual. They should instil giving behaviour and consider themselves as 'the giver'. Experts from financial education and Islamic finance areas are interviewed. Results from Analytic Network Process suggest that setting specific targeted behaviour is the most priority, with debt-taking focus of interest. Women apparently become the most urgent targeted audience of Islamic finance education. Before executing education program, participant’s belief towards Islamic value should be built. Experts suggest formal education institution be the most preferable place to establish the program, in collaboration with formal financial institutions to conduct the training and support from government budget. Introducing Islamic economics and finance values from the earlier stage of formal education would be suitable for future consideration.